Reduced Metabotropic Glutamate Receptor Type 5 Availability in the Epileptogenic Hippocampus: An in vitro Study - Zimmermann, Maria; Minuzzi, Luciano; Aliaga Aliaga, Arturo; Guiot, Marie-Christine; Hall, Jeffery A.; Soucy, Jean-Paul; Massarweh, Gassan; El Mestikawy, Salah; Rosa-Neto, Pedro; Kobayashi, Eliane (Frontiers in Neurology, 2022)
Abnormalities in the expression of metabotropic glutamate receptor type 5 (mGluR5) have been observed in the hippocampus of patients with drug-resistant mesial Temporal Lobe Epilepsy (mTLE). Ex-vivo studies in mTLE hippocampal surgical specimens have shown increased mGluR5 immunoreactivity, while in vivo whole brain imaging using positron emission tomography (PET) demonstrated reduced hippocampal mGluR5 availability. To further understand mGluR5 abnormalities in mTLE, we performed a saturation autoradiography study with [3H]ABP688 (a negative mGluR5 allosteric modulator). We aimed to evaluate receptor density (Bmax) and dissociation constants (KD) in hippocampal mTLE surgical specimens and in non-epilepsy hippocampi from necropsy controls. mTLE specimens showed a 43.4% reduction in receptor density compared to control hippocampi, which was independent of age, sex and KD (multiple linear regression analysis). There was no significant difference in KD between the groups, which suggests that the decreased mGluR5 availability found in vivo with PET cannot be attributed to reduced affinity between ligand and binding site. The present study supports that changes within the epileptogenic tissue include mGluR5 internalization or conformational changes that reduce [3H]ABP688 binding, as previously suggested in mTLE patients studied in vivo.